Usability and value of a digital learning resource in nursing education across European countries: a cross-sectional exploration - Kristin Hjorthaug Urstad; Esther Navarro-Illana; Bjørg Oftedal; Katharine Whittingham; Santiago Alamar; Richard Windle; Atle Løkken; Michael Taylor; Marie Hamilton Larsen; Melanie Narayasanamy; Javier Sancho-Pelluz; Pedro Navarro-Illana; et al. (BMC, 2021)
Abstract Background Higher education is responsible for providing education that meets international benchmarks relevant to the needs of the international community. Due to the increase of digital tools in higher education, the possibility of sharing learning resources across nations has expanded. In the current project, a Norwegian university invited universities in Spain and the United Kingdom to adapt and translate e-learning resources originally developed for Norwegian nursing students for use within their respective Bachelor in Nursing programmes. Aim The aim of the current study was to gain insights into the usability and value for learning of e-compendiums shared and implemented across three European universities. Methods The study adopted a descriptive cross-sectional design and included nursing students from the University of Nottingham, Valencia Catholic University, and the University of Stavanger. Data were collected in Autumn 2017 through a questionnaire adapted from the validated "Centre for Excellence in Teaching and Learning Reusable Learning Object evaluation questionnaire" The questionnaire consisted of 19 items that included two aspects: e-compendiums' value for learning and e-compendiums' usability. The different study sites were compared using a binary logistic regression analysis. Subgroups of students were compared based on their gender and age. Results A total of 480 nursing students participated in the study. The e -compendiums were overall positively rated, especially for reinforcing and retaining knowledge. Compared to the students from the University of Stavanger, students from Valencia Catholic University rated the e-compendiums more positively in most aspects of learning. Students from University of Nottingham found the e-compendiums to be more important for learning engagement compared to students at the Norwegian study site, and no differences were found in any other aspects of learning. Younger students rated the interactivity and visual components as more important compared to older students. Conclusions Students from the University of Nottingham and Valencia Catholic University seem to accept the e-compendiums despite the fact that they were originally developed for use in another country. We argue that, when sharing e-learning resources across countries, an adaptation and translation process that includes a multicultural and multidisciplinary perspective should be carried out.